MHC class II, tumour necrosis factor α, and lymphotoxin α gene haplotype associations with serological subsets of systemic lupus erythematosus. Issue 4 (17th August 2005) - McHugh, N J; Owen, P; Cox, B; Dunphy, J; Welsh, K
Abstract : Objective: To conduct a case–control study to investigate whether there are independent tumour necrosis factor α (TNFα) or lymphotoxin α (LTα) haplotype associations with SLE or with any of the major serological subsets of SLE. Methods: 157 patients with SLE were genotyped for HLA-DRB1, HLA-DQB1, TNFα, and LTα alleles by polymerase chain reaction and compared with 245 normal white controls. For TNFα, six single nucleotide polymorphisms (SNPs) at positions −1031, −863, −857, −308, −238, and +488 and for LTα three SNPs at positions +720, +365, and +249 were studied to assign six TNFα haplotypes (TNF1-6) and four LTα haplotypes (LTA1-4). All SLE patients had full serological profiles on serial samples. Results: The most significant association with SLE overall was with HLA-DR3 (p<0.001; odds ratio (OR) = 2.5 (95% confidence interval, 1.6 to 3.8)) and the extended haplotype HLA-DQB1*0201;DRB1*0301;TNF2;LTA2 (p<0.001; OR = 2.3 (1.4 to 3.7)). Associations were strongest in the anti-La positive group (13%) of SLE patients (HLA-DR3, OR = 71 (9 to 539); HLA-DQB1*0201, OR = 35 (5 to 267); TNF2, OR = 10 (2.8 to 36), and LTA2, OR = 4.9 (1.1 to 21)). There was an increase in the HLA-DR2 associated extended haplotype (HLA-DQB1*0602;DRB1*1501;TNF1;LTA1) in patients with anti-Ro in the absence of anti-La (p<0.005; OR = 3.9 (1.5 to 10)). The HLA-DR7 extended haplotype (HLA-DQB1*0303; DRB1*0701/2; TNF5;LTA3) was decreased in SLE overall (p<0.02; OR = 0.2 (0.05 to 0.8)). Conclusions: The strongest association in this predominantly white population with SLE was between HLA-DR3 and anti-La, which seemed to account for any associations with TNFα alleles on an extended DR3 haplotype.